Mechanisms of Moral Injury Following Military Sexual Trauma and Combat in Post-9/11 U.S. War Veterans - Frankfurt, Sheila B.; DeBeer, Bryann B.; Morissette, Sandra B.; Kimbrel, Nathan A.; La Bash, Heidi; Meyer, Eric C. (Frontiers in Psychiatry, 2018)
Objectives: Moral injury may result from perpetration-based and betrayal-based acts that violate deeply held norms; however, researchers and clinicians have little guidance about the moral injury syndrome’s specific developmental pathways following morally injurious events. The present study’s objective was to examine the direct and indirect pathways proposed in a frequently cited model of moral injury (Litz et al., 2009) in relation to two types of military-related traumas [experiencing military sexual trauma (MST) and combat exposure]. Methods: Secondary analyses were conducted within a sample of post-9/11 veterans at a Southwestern Veterans Health Care System (N = 310) across two time-points. Structural equation modeling tested the direct and indirect pathways from MST and combat to a PTSD-depression factor via betrayal, perpetration, guilt, and shame. Results: Betrayal accounted for the association between MST and PTSD-depression (β = .10, p < .01, 95% CI = .01 - .11) and perpetration accounted for the association between combat and PTSD-depression (β = .07, p < .05, 95% CI = .02 - .14). The indirect path from combat to shame to PTSD-depression was significant (β = .16, p < .01, 95% CI = .07 - .28) but the path through guilt was not. The specific indirect paths through perpetration or betrayal to shame or guilt were nonsignificant. Conclusions: Betrayal and perpetration are associated with PTSD-depression following MST and combat. Results suggest multiple pathways of moral injury development following different military traumas and morally injurious events. Implications for moral injury conceptualization and treatment are discussed.